SELF-REPORTED VISION IMPAIRMENT AND SUBJECTIVE WELL-BEING IN OLDER ADULTS: A LONGITUDINAL MEDIATION ANALYSIS. (8th November 2019) - Ehrlich, Joshua R; Xiang, Xiaoling; Shah, Khushali; Hu, Rita X; Stagg, Brian C; Freedman, Vicki A
Abstract: Vision impairment (VI) in older adults is associated with declines in well-being. However, the pathways through which poor vision leads to declines in well-being have not been well described. The purpose of this study was to determine whether activity limitations and social participation restrictions mediate the impact of self-reported VI on subjective well-being. This study used data from the National Health and Aging Trends Study (NHATS), a nationally-representative longitudinal study of Medicare beneficiaries 65 and older that includes detailed measures of the disablement process. We conceptualized a longitudinal mediation model linking self-reported VI and subjective well-being. Structural equation modeling was used to test the mediating effects of activity limitations and social participation restrictions while adjusting for covariates. The final sample included 5, 431 respondents. At baseline, 8.0% of Medicare beneficiaries had self-reported VI. Subjective well-being scores were significantly lower among respondents with self-reported VI (15.7, 95% CI=15.2, 16.2) compared to those without VI (17.6, 95% CI=17.5, 17.7). Self-reported VI had a significant indirect effect on subjective well-being through limiting mobility (β=-.04, 95% CI=-.07, -.03) and household activities (β=-.05, 95% CI=-.08, -.03), but not self-care limitations (β=0.0, 95% CI=0.0, 0.0) or participation restrictions (β=0.0, 95% CI=-0.01, 0.00). Total indirect effects from all mediation paths accounted for 42% of the effect of VI on well-being. In conclusion, mobility and household activity limitations are significant mediators that explain a considerable portion of the impact of poor vision on well-being. Interventions to promote successful accommodation may result in greater well-being for visually impaired older adults.